Profile of Policystic Ovarian Syndrome Patients in Dr. Cipto Mangunkusumo General Hospital Jakarta March 2009 - March 2010 - Pangastuti, Niken P. (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To study phenotype profile and correlation between fasting blood glucose-fasting insulin ratio and luteinizing hormonefollicle stimulating hormone ratio with free androgen index in polycycstic ovarian syndrome in Dr. Cipto Mangunkusumo Hospital Jakarta. Method: A descriptive cross-sectional study was carried out at Dr. Cipto Mangunkusumo General Hospital Jakarta in March 2009 - March 2010, using secondary data, were involved 105 reproductive age women who has been diagnosed as PCOs with Rotterdam criteria. History of the subjects was taken from medical record that consist of interview result about menstrual history and clinical manifestations of hyperandrogenemia and clinical, biochemical, and ovarian ultrasound assessment. Result: From 105 women were identified, 100 women with oligo/amenorrhea (94.2%) and 34 women with hirsutism (32.4%). Further evaluation of the 105 cases, it was identified 80% subjects with polycystic ovaries morphology, 34.3% with hyperandrogenemia, 71.4% with insulin resistant, and 66.7% with increasing LH and FSH ratio. While, the most symptom and sign combination is oligo/amenorrhea and polycystic ovaries morphology, that is 44.8%. With Spearman non parametric correlation test, there were a significant correlation between fasting blood glucose-fasting insulin ratio and free androgen index (FAI) with coefficient of correlation -0.342 and and between LH/FSH and FAI with coefficient of correlation 0.386. Conclusion: The most common symptom and sign of PCOs patients in this study were oligo/amenorrhea and polycystic ovaries and insulin resistant. There were significant correlations between fasting blood glucose-fasting insulin ratio and LH/FSH with FAI. [Indones J Obstet Gynecol 2011; 35-1: 8-13] Keywords: polycystic ovarian syndrome, insulin resistance, luteinizing hormone hypersecretion, hyperandrogenemia